Optical voice information hiding using enhanced iterative algorithm and computational ghost imaging. (23rd May 2019) - Kumar, Ravi; Zhong, Fuqiang; Quan, Chenggen
Abstract: Recently, optical techniques have been studied extensively for securing grayscale and colour images. However, at the present time, a lot of sensitive information has also been transmitted in the form of audio/voice signals, thus, the development of secure optical transmission systems for voice signals is also very important. In this paper, we present a new optical cryptosystem for the secure transmission of voice/audio signals. The voice information is distributed among two phase masks and a security image using the enhanced iterative approach. In that, the 2D non-separable linear canonical transform ( NS-LCT ) is utilized. 2D NS-LCT is defined using ten independent parameters, all of which can be used as the security keys for the cryptosystem. Also, the security image containing the voice information can be further processed through optical encryption systems, which add an extra layer of security. The numerical simulation results are presented to demonstrate the validity and efficiency of the proposed method.